New insights into the pathophysiology and therapeutic targets of asthma and comorbid chronic rhinosinusitis with or without nasal polyposis - Striz, Ilja; Golebski, Kornel; Strizova, Zuzana; Loukides, Stelios; Bakakos, Petros; Hanania, Nicola A; Jesenak, Milos; Diamant, Zuzana (Clinical science (London, England, 2023)
Asthma and chronic rhinosinusitis with nasal polyps (CRSwNP) or without (CRSsNP) are chronic respiratory diseases. These two disorders often co-exist based on common anatomical, immunological, histopathological, and pathophysiological basis. Usually, asthma with comorbid CRSwNP is driven by type 2 (T2) inflammation which predisposes to more severe, often intractable, disease. In the past two decades, innovative technologies and detection techniques in combination with newly introduced targeted therapies helped shape our understanding of the immunological pathways underlying inflammatory airway diseases and to further identify several distinct clinical and inflammatory subsets to enhance the development of more effective personalized treatments. Presently, a number of targeted biologics has shown clinical efficacy in patients with refractory T2 airway inflammation, including anti-IgE (omalizumab), anti-IL-5 (mepolizumab, reslizumab)/anti-IL5R (benralizumab), anti-IL-4R-α (anti-IL-4/IL-13, dupilumab), and anti-TSLP (tezepelumab). In non-type-2 endotypes, no targeted biologics have consistently shown clinical efficacy so far. Presently, multiple therapeutical targets are being explored including cytokines, membrane molecules and intracellular signalling pathways to further expand current treatment options for severe asthma with and without comorbid CRSwNP. In this review, we discuss existing biologics, those under development and share some views on new horizons.
Keywords: nosní polypy; sinusitida; Asthma; bronchiální astma; Humans; Chronic Disease; Inflammation; komorbidita; lidé; asthma; chronic rhinosinusitis; precision medicine; zánět; rýma; biologics; Nasal Polyps; type 2 inflammation; Comorbidity; chronická nemoc; Sinusitis; biologické přípravky; airway remodelling; Rhinitis; Biological Products